COMPOSITIONAL AND WEATHERABILITY INDICES OF GETSO KAOLIN DEPOSITS FOR POZZOLANA PRODUCTION - Aliyu, Hassan; Mohammed, A. K.; KofarBai, S. A.; Muhammad, K. R. (FUDMA Journal of Sciences, 2024)
Kaolin is an aluminio-silicate mineral naturally distributed within the earth’s crust formed from the weathering of rich feldspartic rocks. The compositional requirements of Getso kaolin deposits for pozzolana production have been carried out. The kaolin deposits were hosted by the rhyolitic rocks of the basement complex of North-Western Nigeria. Three samples from each five locations at different depths were collected and analysed using Free Swelling Ratio (FSR), Free Swelling Index (FSI), X-Ray Fluorescence Spectrometry (XRF) and Scanning Electron Microscopy/Electron Dispersive X-Ray spectroscopy (SEM/EDS). The FSI and FSR ranged between 0-6-0.9 and 16-36 revealing non-swelling and non-expansive Kaolinitic material. The XRF results showed the average concentration of SiO2+ Al2O3+Fe2O3: point 1 (78.99 wt.%); point 2 (78.62 wt.%); point 3 (79.14 wt.%); point 4 (80.10 wt.%) and point 5 (80.0 wt.%) suggested to be classified as N pozzolana (ASTMC 618). The Fe2O3/MgO versus SiO3 indicated the samples were products of the calc-alkaline series which is an indication of light colour kaolin deposits. The computed Chemical Index of Alteration (CIA: 91.34), Chemical Index of Weatheribility (CIW: 98.13), Index of compositional variability (CIV: 0.29), Silica Modulus Ratio (SM: 1.77), Lime Silica Ratio (LSR: 0.14) and Aluminum Iron Ratio (AIR: 30.0) indicated very strong weathering intensity high matured, high silica moderate aluminum and less ferrite. The studied kaolin could be utilized for the production of pozzolana after its being beneficiated to remove the TiO2.
Keywords: Deposits; Feldspar; Major oxides; Weathering intensity